2019
DOI: 10.4034/pboci.2019.191.39
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Repair in the Mandible of Rabbits Using Biphasic Calcium Phosphate Micro-Macroporous Hydroxyapatite Bioceramics and Beta-Tricalcium Phosphate

Abstract: Objective: To perform a clinical and histological evaluation, characterizing and proving the feasibility of the use of beta tricalcium phosphate (HA/βTCP) bioceramics as a bone defect repair material, comparing it with autogenous bone and blood clot in terms of osteoinductive, conductive, and genic capacities. Material and Methods: The experiment was based on 3 critical defects in the mandible of 11 New Zealand rabbits. The defects were filled with HA/βTCP bioceramics and autogenous bone, respectively, collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Fatma Elsherbini, Mohamed Abdulrahman, Mohamed Mostafa El-Shennawi sites, which could be attributed to β-TCP's behavior by acting as a scaffold, on which new bone grew. Franceschini et al [43] agreed with the above by studying the repair of bony defects using β-TCP. They reported improved results.…”
Section: Discussionsupporting
confidence: 53%
“…Fatma Elsherbini, Mohamed Abdulrahman, Mohamed Mostafa El-Shennawi sites, which could be attributed to β-TCP's behavior by acting as a scaffold, on which new bone grew. Franceschini et al [43] agreed with the above by studying the repair of bony defects using β-TCP. They reported improved results.…”
Section: Discussionsupporting
confidence: 53%
“…They form close contact with the tissue and the graft [ 244 ]. The inorganic bioactive materials, such as calcium silicate, hydroxyapatite, bioactive glass, amorphous calcium phosphate, etc., have successfully restored maxillo-facial bone defect after root-end resection and removal of granulation tissue [ 245 , 246 , 247 ]. In a clinical trial study [ 248 ], carbonated hydroxyapatite and Bio-Oss ® —Geistlich Biomaterials, Wolhuser, Switzerland) were placed after extraction, and a histological analysis of bone samples was completed after 90 days.…”
Section: Clinical Applications Of Bioactive Inorganic Materials In De...mentioning
confidence: 99%
“…Unfortunately, the current 3D-printed scaffolds for bone augmentation are ordinary bone defect repair scaffolds, and there is no specific design for the osteogenic characteristics of bone augmentation. The existing research has shown that the osteogenesis of vertical bone augmentation is often associated with an increase in pore diameter ( Franceschini Neto et al, 2019 ; Ghayor et al, 2021 ). More importantly, it has been observed that the optimal microarchitecture for bone augmentation differs from the optimal one for a general bone defect repair ( Jiang et al, 2018 ; Vaquette et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%